Supraventricular tachycardia in one of the twins: The ethical dilemmas involved in treatment - Vinoth Doraiswamy; Lalitha Natarajan; Chitra TV Venkatesh (Wolters Kluwer Medknow Publications, 2020)
The pediatric cardiologist now has an important role to play in fetal medicine. They are often called upon to manage fetal cardiac problems such as arrhythmias or perform fetal cardiac interventions such as balloon valvuloplasty or atrial septostomy. In these scenarios, it becomes very important for the pediatric cardiologist to understand the concepts of "fetus as a patient," "viability," etc., and their implications in management. We try to shed light on these principles through our case scenario of managing supraventricular tachycardia in one of the fetuses of a twin pregnancy.